2016
DOI: 10.1186/s12889-016-3333-1
|View full text |Cite|
|
Sign up to set email alerts
|

The GOOD life: Study protocol for a social norms intervention to reduce alcohol and other drug use among Danish adolescents

Abstract: BackgroundIt is currently unknown if school-based social norms interventions are effective in preventing harmful alcohol consumption and other drug use among adolescents in Denmark. This paper describes the social norms-based programme The GOOD life and the design of a cluster-randomized controlled trial to test its effectiveness.Methods/DesignThe intervention The GOOD life is composed of three social norms components representing three different communication channels, namely face-to-face communication (norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…To facilitate ownership among the pupils each message reflected a positive behaviour of the majority and it was emphasised that the data displayed were specifically tailored for each participating school and grade. The social norms messages were phrased to challenge misperceptions of peer behaviour (descriptive norms) and attitudes towards alcohol use (injunctive norms), such as “8 out of 10 pupils in 8 th grade at [school name] have NEVER been drunk” and “89% of pupils in 8 th grade at [school name] think it's NOT okay to drink alcohol if it affects school ( Stock et al, 2016 ). At each school, The GOOD Life intervention started with a 40-min classroom feedback session facilitated by the research team.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate ownership among the pupils each message reflected a positive behaviour of the majority and it was emphasised that the data displayed were specifically tailored for each participating school and grade. The social norms messages were phrased to challenge misperceptions of peer behaviour (descriptive norms) and attitudes towards alcohol use (injunctive norms), such as “8 out of 10 pupils in 8 th grade at [school name] have NEVER been drunk” and “89% of pupils in 8 th grade at [school name] think it's NOT okay to drink alcohol if it affects school ( Stock et al, 2016 ). At each school, The GOOD Life intervention started with a 40-min classroom feedback session facilitated by the research team.…”
Section: Methodsmentioning
confidence: 99%
“…The web application was designed for individual users and, like the feedback session, the setup involved a multiple-choice quiz that instantly showed the correct answer. The web application was developed by Social Sense Ltd. (UK), modified for use in The GOOD Life in close collaboration with the research team ( Stock et al, 2016 ) and used in accordance to a temporary licence agreement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, The Good Life Study used three communication channels (face-to-face, print, and web-based communication) to provide normative messages about alcohol and drug use to public schools over a period of 8 weeks in Denmark. 19 However, not all interventions based on changing social norms have been able to change behaviors. In a national evaluation of a social norm intervention of almost 100 colleges targeting alcohol consumption, researchers found that students attending colleges that adopted the social norms marketing were not different in 7 measures of alcohol consumption (eg, daily and 30-day use, heavy episodic drinking, drunkenness), compared to students in schools that did not adopt the social norms marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of this study design article [ 1 ], it has come to our attention that some terminology was inconsistently used in the article. The GOOD life trial uses a definition of binge drinking of “5 or more drinks on one occasion” in accordance with the ESPAD study [ 2 ].…”
Section: Erratummentioning
confidence: 99%